Factors influencing public satisfaction with the local police: a study in Saskatoon, Canada. Issue 4 (16th November 2015) - Cheng, Hongming
Abstract : Purpose: – The purpose of this paper is to explore determining factors that account for variation in public satisfaction with the local police in Saskatoon, Saskatchewan, Canada. Design/methodology/approach: – An integrated method was used to gather the data for this study, including official survey data conducted by Insightrix, and interviews with citizens in Saskatoon. Findings: – This research found that demographic factors including age, race (in this study, Aboriginal status in particular), education, and income, perception of neighborhood safety, citizen-police interaction, and learning about crime from news media all have impact on public attitudes toward the police, to different degrees. The gap or distance between the police and the Aboriginal community was highlighted as a major factor. Research limitations/implications: – Further research should be done to compare statistical patterns in other same-level cities in Canada. Practical implications: – This paper indicates that Saskatoon Police Service in the future should provide a more structured avenue for citizen participation in establishing safe neighborhoods, more structured cultural sensitivity training, and create a wider channel through which community residents with various social backgrounds can demand some measure of accountability for police work in their area. Originality/value: – The paper is of value to law enforcement policy-makers and academic researchers with interest in policing and police-community relationship.